2014
DOI: 10.1158/0008-5472.can-14-0927
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides Drive the Tumor Infiltration and Function of Myeloid-Derived Suppressor Cells

Abstract: While it is now widely appreciated that anti-tumor immunity is critical to impede tumor growth and progression, there remain significant gaps in knowledge about the mechanisms used by tumors to escape immune control. In tumor cells, we hypothesized that one mechanism of immune escape used by tumors involves the synthesis and extracellular shedding of gangliosides, a class of biologically active cell surface glycosphingolipids with known immunosuppressive properties. In this study, we report that tumor cells en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…Following FGF binding to FGFR and heterodimerization, the tyrosine kinase domains phosphorylate each other, leading to the activation of key downstream pathways. b Examples of FGF/FGFR inhibitors; asterisk denotes FDA-approved drugs in cancer; Ab = Antibody; FP-1039 (GSK3052230) is a ligand trap, i.e., sequesters FGFs and inhibits their signaling [ 71 ]. c The interactions between FGFs and FGFRs; references: Guillemot et al [ 32 ], Powers et al [ 191 ], Ornitz et al [ 192 ], Zhang et al [ 34 ].…”
Section: Molecular Biology Of Fgf/fgfr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Following FGF binding to FGFR and heterodimerization, the tyrosine kinase domains phosphorylate each other, leading to the activation of key downstream pathways. b Examples of FGF/FGFR inhibitors; asterisk denotes FDA-approved drugs in cancer; Ab = Antibody; FP-1039 (GSK3052230) is a ligand trap, i.e., sequesters FGFs and inhibits their signaling [ 71 ]. c The interactions between FGFs and FGFRs; references: Guillemot et al [ 32 ], Powers et al [ 191 ], Ornitz et al [ 192 ], Zhang et al [ 34 ].…”
Section: Molecular Biology Of Fgf/fgfr Signalingmentioning
confidence: 99%
“…Of interest, other types of agents have been developed. As an example, FP-1039 is a soluble fusion protein, consisting of the extracellular domains of human FGFR1 linked to the Fc region of the human immunoglobulin G1; it is designed to bind multiple FGF ligands [ 71 ] (TRAP molecule).…”
Section: Fgf/fgfr Signaling Inhibitors and Cancer Therapymentioning
confidence: 99%
“…They have also been shown to induce apoptosis in T cells ( 90 ) and dendritic cells ( 134 ), and impair antigen presentation in human monocytes ( 135 ). In a tumor model engineered to lack GM3, GM2, GM1, and GD1a, the observed impairment of tumor growth was attributed to a reduction, and decreased activity, of MDSCs ( 136 ). Intriguingly, the presence of MDSCs could be restored by exogenous supplementation of gangliosides which suggests a direct connection between tumor-produced gangliosides and the recruitment of immunosuppressive MDSCs to the TME.…”
Section: Gangliosides As Part Of the Tumor “Glycocode”mentioning
confidence: 99%
“…Tumor-associated gangliosides are also shed to microenvironment and detected in sera of cancer patients. There, they can affect functions of immune cells, e.g., inhibit CTL cytotoxicity and on the contrary attract myeloid derived suppressor cells [30,31]. Finally, in 2014, Liu et al showed that gangliosides enhance tumor angiogenesis, by comparing tumor vasculature generated in mice by wild type and GM3 synthase/GM2 synthase deficient embryonic fibroblasts that were stably transfected with c-myc and H-Ras.…”
Section: Gangliosides Are Tumor-associated Antigensmentioning
confidence: 99%